2015
DOI: 10.7717/peerj.819
|View full text |Cite
|
Sign up to set email alerts
|

Found in transition: applying milestones to three unique discharge curricula

Abstract: Introduction. A safe and effective transition from hospital to post-acute care is a complex and important physician competency. Milestones and Entrustable Professional Activities (EPA) form the new educational rubric in Graduate Medical Education Training. “A safe and effective discharge from the hospital” is an EPA ripe for educational innovation.Methods. The authors collaborated in a qualitative process called mapping to define 22 of 142 Internal Medicine (IM) curricular milestones related to the transition … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Our program follows Kripalani and Weiss [34] recommendations for teaching health literacy education, including meeting patients and receiving feedback for the communication they practice, and contains the two main milestones for safe transition in care identified by Meade et al [23] i.e. patient-centeredness and use of succinct written communication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our program follows Kripalani and Weiss [34] recommendations for teaching health literacy education, including meeting patients and receiving feedback for the communication they practice, and contains the two main milestones for safe transition in care identified by Meade et al [23] i.e. patient-centeredness and use of succinct written communication.…”
Section: Discussionmentioning
confidence: 99%
“…Directed at another doctor and using language rich in medical terminology and jargon, it is indecipherable to most lay people. Intervention programs aimed at improving the safety and quality of transition in care address this gap by emphasizing the importance of clear communication [22,23] and through design of personalized discharge letters [24].…”
Section: Introductionmentioning
confidence: 99%
“…Previous interventions have taught transitions from hospital to home to a range of learners, from preclinical medical students to attending physicians and allied health professionals. 18,[20][21][22] Most of them found that a clinically oriented curriculum for medical students improved their interdisciplinary collaboration and transitional care knowledge. 21,22 However, there have been few curricular on how to transition critically ill children from PICU to wards.…”
Section: Introductionmentioning
confidence: 99%